Travel Motivation, Destination Image, and Stage of Intention to Visit Anak Krakatau Mount: a Study of Volcano Tourism in Indonesia - Suhud, Usep; Allan, Mamoon (Anuário do Instituto de Geociências, 2022)
This study aims to measure the impact of travel motivation and destination image on stage of intention to visit a volcano site, particularly Anak Krakatau. "Anak" means "child". This mount is a volcano created by the deadly eruption of the Krakatau volcano which killed 36,417 people in 1883 and had a wide-ranging impact on some of the world's ecosystems. This mountain is located on a small island between two large islands of Sumatra and Java, Indonesia. Anak Krakatau is more popular among domestic tourists. Data were collected using an online questionnaire platform and the study used a convenience sample of 250 participants. Data were analysed using exploratory and confirmatory factor analyses, as well as structural equation model. Stage intention consisted of visit intention in the period of one, three, and five years and each of them were treated as individual variable unless for visit intention in a year due to insignificance. As a result, travel motivation had a significant impact on destination image and destination image significantly affects stage of intention.